Hesitancy as ethics - Kofoed, Jette; Staunæs, Dorthe (Reconceptualizing Educational Research Methodology, 2015)
In this paper we suggest hesitancy as ethics as a research strategy for researchers in the midst of fieldwork. We focus on the uncomfortable, unclear and uncertain aspects of researcher subjectification in fieldwork and argue that such uncertainty promises potential when it comes to stipulating ethical requirements and strategies. The suggested strategy involves assuming uncertainty as part of the researcher’s position and approach, as well as insisting that research also includes an ethical obligation to ‘not be too certain’. In the paper we expand upon this by suggesting five possible components of a different kind of intervention into fieldwork in what we label high intensity zones.